Henry Golerick, Charter and Revised Ordinances of the City of Fort Wayne 26 (1887) - (:unkn) unknown (My University, 1887)
Ch. 31, § 17: It shall be unlawful for any person to fire or discharge any common gun, fowling piece, pistol or firearms of any description, or fire, or explode or set off any squib, cracker, or any other thing containing powder, or other combustible or explosive material, without permission from the Common Council, or written permission from the Mayor
Keywords: DISCHARGE